Perbedaan Kelas Sosial sebagai Penyebab Ijime dalam Novel Grotesque - Linda Unsriana (Bina Nusantara University, 2012)
Ijime or bullying is a common problem in Japanese schools, and even, ijime actions sometimes result in the victims or the victims commit to suicide. Ijime is also depicted in the Grotesqe novel on a character, Kazue Sato. Kazue Sato is a girl who desperately wants to enroll an elite girl school, Q school. The school is for students from high social class. Nevertheless, by passing the strict exams, intelligent students from different social classes can go to this school. Article elaborates the relationship between social class differences in the actions of ijime, using a corpus of works Natsuo Kirino’s novel, Grotesque. After analyzing the data with descriptive method of analysis, it is found that there is a relationship between social class differences and ijime actions. Students from different social classes, although they are cleverer, cannot mingle with students from higher social classes. In fact, students from lower social classes experience ijime actions from other students.